Analysis of synonymous codon usage patterns in mitochondrial genomes of nine Amanita species - Li, Qiang; Luo, Yingyong; Sha, Ajia; Xiao, Wenqi; Xiong, Zhuang; Chen, Xiaodie; He, Jing; Peng, Lianxin; Zou, Liang (Frontiers in Microbiology, 2023)
In the present study, we analyzed the base bias of 12 mitochondrial core protein coding genes (PCGs) shared by 9 Amanita species. The results showed that the codons of all Amanita species tended to end in A/T, demonstrating the preference of mitochondrial codons of Amanita species for a preference for this codon. In addition, we detected the correlation between codon base composition and the codon adaptation index (CAI), codon bias index (CBI) and frequency of optimal codons (FOP) indices, indicating the influence of base composition on codon bias. The average effective number of codons (ENC) of mitochondrial core PCGs of Amanita is 30.81, which is <35, demonstrating the strong codon preference of mitochondrial core PCGs of Amanita. The neutrality plot analysis and PR2-Bias plot analysis further demonstrated that natural selection plays an important role in Amanita codon bias. In addition, we obtained 5-10 optimal codons (ΔRSCU>0.08 and RSCU>1) in 9 Amanita species, and GCA and AUU were the most widely used optimal codons. Based on the combined mitochondrial sequence and RSCU value, we deduced the genetic relationship between different Amanita species and found large variations between them. This study promoted the understanding of synonymous codon usage characteristics and evolution of this important fungal group.